Monetary and Social Incentives in Multi-Tasking: The Ranking Substitution Effect - Matthias Stefan; Jürgen Huber; Michael Kirchler; Matthias Sutter; Markus Walzl (Institute of Labor Economics (IZA), 2020)
Rankings are prevalent information and incentive tools in labor markets with strong competition for talent. In a dynamic model of multi-tasking and an accompanying experiment with financial professionals, we identify hidden ranking costs when performance in one task is incentivized and ranked while another prosocial task is not: (i) a ranking influences behavior if individuals lag behind: they spend more total effort and substitute effort in the prosocial task with effort in the ranked task; (ii) those ahead in the ranking spend less total effort and lower relative effort in the ranked task. Implications for incentive schemes are discussed.
Keywords: C93; D02; D91; 330; multi-tasking decision problem; rank incentives; framed field experiment; finance professionals